Studying Effective Factors on Overweight and Obesity in High School Students in Erbil - Sarhang Qadir Ibrahim1 , Tariq S. Al- Hadithi2 , Kameran Hassan Ismail3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Overweight and obesity are explained as excessive fat depositions in human body. They have become one of the serious public health problems of the twenty-first century in low income countries. The prevalence of overweight and obesity in children is increasing worldwide, and currently 1 child in 10 is overweight or obese. The aim of this study was to assess overweight and obesity and associated factors in high school students in Erbil.Method: It was a cross-sectional study in which 1,000 students in the age range 16-18 years of Erbil, Iraq in 2016-2017 were randomly selected. Data were gathered by a questionnaire. Data were analyzed using SPSS version 22 by appropriate statistical tests.Results: our results showed that some effective factors such as Computer games, watching TV, and irregular sleep (P-value<0.05) were the known factors/ affecting obesity/overweight in this study.Conclusion: This study revealed that there are many factors involved in emerging over weight, such as overeating, eating snacks just before bedtime, and eating between meals especially between dinner and bed time, having lunch/dinner outside at restaurants and eating rice frequently, taking a nap during the day and watching TV/play video games/computer games.